2020
DOI: 10.1186/s41065-020-00162-w
|View full text |Cite
|
Sign up to set email alerts
|

Population genomics of East Asian ethnic groups

Abstract: East Asia constitutes one-fifth of the global population and exhibits substantial genetic diversity. However, genetic investigations on populations in this region have been largely under-represented compared with European populations. Nonetheless, the last decade has seen considerable efforts and progress in genome-wide genotyping and whole-genome sequencing of the East-Asian ethnic groups. Here, we review the recent studies in terms of ancestral origin, population relationship, genetic differentiation, and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…For example, East Asians are commonly known to endorse collectivist culture, and White Americans, to support individualist culture (Ran et al, 2021). The largest population in East Asians is Chinese, followed by Japanese and Korean (Pan & Xu, 2020). Pang et al (2017) found that Chinese Singaporeans suffering from mental illnesses experienced a higher level of social distance and physical threat connected to the influence of collectivism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, East Asians are commonly known to endorse collectivist culture, and White Americans, to support individualist culture (Ran et al, 2021). The largest population in East Asians is Chinese, followed by Japanese and Korean (Pan & Xu, 2020). Pang et al (2017) found that Chinese Singaporeans suffering from mental illnesses experienced a higher level of social distance and physical threat connected to the influence of collectivism.…”
Section: Discussionmentioning
confidence: 99%
“…The largest population in East Asians is Chinese, followed by Japanese and Korean (Pan & Xu, 2020). Pang et al (2017) found that Chinese Singaporeans suffering from mental illnesses experienced a higher level of social distance and physical threat connected to the influence of collectivism.…”
Section: Ta B L E 2 (Continued)mentioning
confidence: 99%
“…However, the genetic origin and history of most minorities living in Yunnan are still opaque. A comparison of the genetic backgrounds and evolutionary histories of Yunnan minorities is required to uncover the human genetic diversity [4].…”
Section: Introductionmentioning
confidence: 99%
“…The genetic background between the Thai and Chinese populations is substantially different. The Thai population is highly diversified in reflecting its genetic admixture with its neighboring population [ 61 ], whereas the Chinese population is relatively homogeneous in reflecting its relative stable evolutionary path in the East Asia region although having extensive internal heterogeneity [ 62 , 63 ]. The same analytic conditions and extensive filtering of normal genetic polymorphism used in the two studies provided a quality control to ensure the reliability of the mutation data derived for the comparison between the two TNBC cohorts.…”
Section: Discussionmentioning
confidence: 99%